Interferon-β promotes macrophage foam cell formation by altering both cholesterol influx and efflux mechanisms. (January 2016) - Boshuizen, Marieke C.S.; Hoeksema, Marten A.; Neele, Annette E.; van der Velden, Saskia; Hamers, Anouk A.J.; Van den Bossche, Jan; Lutgens, Esther; de Winther, Menno P.J.
Graphical abstract: Highlights: IFNβ increases macrophage lipid uptake mediated via SR-A in vitro and in vivo. IFNβ treatment in vitro decreases macrophage cholesterol efflux via ABCA1. IFNβ promotes macrophage foam cell formation, confirming its pro-atherogenic role. Abstract: Foam cell formation is a crucial event in atherogenesis. While interferon-β (IFNβ) is known to promote atherosclerosis in mice, studies on the role of IFNβ on foam cell formation are minimal and conflicting. We therefore extended these studies using both in vitro and in vivo approaches and examined IFNβ's function in macrophage foam cell formation. To do so, murine bone marrow-derived macrophages (BMDMs) and human monocyte-derived macrophages were loaded with acLDL overnight, followed by 6 h IFNβ co-treatment. This increased lipid content as measured by Oil red O staining. We next analyzed the lipid uptake pathways of IFNβ-stimulated BMDMs and observed increased endocytosis of DiI-acLDL as compared to controls. These effects were mediated via SR-A, as its gene expression was increased and inhibition of SR-A with Poly(I) blocked the IFNβ-induced increase in Oil red O staining and DiI-acLDL endocytosis. The IFNβ-induced increase in lipid content was also associated with decreased ApoA1-mediated cholesterol efflux, in response to decreased ABCA1 protein and gene expression. To validate our findings in vivo, LDLR −/− mice were put on chow or a high cholesterol diet for 10 weeks. 24 and 8 h before sacrifice mice were injected with IFNβ or PBS, after which thioglycollate-elicited peritoneal macrophages were collected and analyzed. In accordance with the in vitro data, IFNβ increased lipid accumulation. In conclusion, our experimental data support the pro-atherogenic role of IFNβ, as we show that IFNβ promotes macrophage foam cell formation by increasing SR-A-mediated cholesterol influx and decreasing ABCA1-mediated efflux mechanisms.